A comparison study of stem taper material loss at similar and mixed metal head-neck taper junctions. (October 2017) - Langton, D. J.; Sidaginamale, R. P.; Joyce, T. J.; Meek, R. D.; Bowsher, J. G.; Deehan, D.; Nargol, A. V. F.; Holland, J. P.
Abstract : Aims: We sought to determine whether cobalt-chromium alloy (CoCr) femoral stem tapers (trunnions) wear more than titanium (Ti) alloy stem tapers (trunnions) when used in a large diameter (LD) metal-on-metal (MoM) hip arthroplasty system. Patients and Methods: We performed explant analysis using validated methodology to determine the volumetric material loss at the taper surfaces of explanted LD CoCr MoM hip arthroplasties used with either a Ti alloy (n = 28) or CoCr femoral stem (n = 21). Only 12/14 taper constructs with a rough male taper surface and a nominal included angle close to 5.666° were included. Multiple regression modelling was undertaken using taper angle, taper roughness, bearing diameter (horizontal lever arm) as independent variables. Material loss was mapped using a coordinate measuring machine, profilometry and scanning electron microscopy. Results: After adjustment for other factors, CoCr stem tapers were found to have significantly greater volumetric material loss than the equivalent Ti stem tapers. Conclusion: When taper junction damage is identified during revision of a LD MoM hip, it should be suspected that a male taper composed of a standard CoCr alloy has sustained significant changes to the taper cone geometry which are likely to be more extensive than those affecting a Ti alloy stem. Cite this article: Bone Joint J 2017;99-B:1304–12.